Structure, mechanism, and evolution of the last step in vitamin C biosynthesis - Boverio, Alessandro (2024)
Photosynthetic organisms, fungi, and animals comprise distinct pathways forvitamin C biosynthesis. Besides this diversity, the ﬁnal biosynthetic step con-sistently involves an oxidation reaction carried out by the aldonolactone oxi-doreductases. Here, we study the origin and evolution of the diversiﬁedactivities and substrate preferences featured by these ﬂavoenzymes usingmolecular phylogeny, kinetics, mutagenesis, and crystallographic experi-ments. We ﬁnd clear evidence that they share a common ancestor. A ﬂavin-interacting amino acid modulates the reactivity with the electron acceptors,including oxygen, and determines whether an enzyme functions as an oxidaseor a dehydrogenase. We show that a few side chains in the catalytic cavityimpart the reaction stereoselectivity. Ancestral sequence reconstruction out-lines how these critical positions were afﬁxed to speciﬁc amino acids along theevolution of the major eukaryotic clades. During Eukarya evolution, thealdonolactone oxidoreductases adapted to the varying metabolic demandswhile retaining their overarching vitamin C-generating function.